Explaining psychological insulin resistance in adults with non-insulin-treated type 2 diabetes: The roles of diabetes distress and current medication concerns. Results from Diabetes MILES—Australia. Issue 1 (February 2016) - Holmes-Truscott, E.; Skinner, T.C.; Pouwer, F.; Speight, J.
Highlights: Cross-sectional study exploring factors associated with negative insulin therapy appraisals. Insulin appraisals moderately associated with diabetes-specific emotional-burden. Insulin appraisals moderately associated with concerns about diabetes medications. Weaker associations observed with general medication beliefs and wellbeing. Interventions should look to improve diabetes-specific distress and medicine beliefs. Abstract: Aims: To investigate the contribution of general and diabetes-specific emotional wellbeing and beliefs about medicines in the prediction of insulin therapy appraisals in adults with non-insulin-treated type 2 diabetes. Methods: The sample included Diabetes MILES–Australia cross-sectional survey participants whose primary diabetes treatment was oral hypoglycaemic agents ( N = 313; 49% women; mean ± SD age: 57 ± 9 years; diabetes duration: 7 ± 6 years). They completed validated measures of beliefs about the 'harm' and 'overuse' of medications in general (BMQ General); 'concerns' about and 'necessity' of current diabetes medications (BMQ Specific); negative insulin therapy appraisals (ITAS); depression (PHQ-9); anxiety (GAD-7), and diabetes distress (DDS-17). Factors associated with ITAS Negative scores were examined using hierarchical multiple regressions. Results: Twenty-two percent of the variance in ITAS Negative scores (52 ± 10), was explained by: number of complications ( β = −.15, p = .005), DDS-17 subscale 'emotional burden' ( β = .23, p < .001), and 'concerns' about current diabetes treatment ( β = .29, p < .001). General beliefs about medications and general emotional wellbeing did not contribute significantly to the model. Conclusions: Psychological insulin resistance may reflect broader distress about diabetes and concerns about its treatment but not general beliefs about medicines, depression or anxiety. Reducing diabetes distress and current treatment concerns may improve attitudes towards insulin as a potential therapeutic option.